Critical Pedagogy in the light of Frankfurt's critical theory - Ramalho, Ayza Rafaela Damasceno; Freitas, Isabel Ferreira; Menezes, Anderson de Alencar (Universidade Estadual de Campinas, 2022)
The present study aims to understand how current collaborations seek to elaborate renewed standard models, based on the investigations of society's present time and on the conceptions of the indispensable causes of Critical Theory. The research stands out as a qualitative research with an exploratory scope and approaches the Critical Theory of the Frankfurt philosopher Theodor W. Adorno. The results achieved with an analysis show an emergence of an education based on sensitivity and humanization to break the cycle of violence present in current educational models.